CRITICAL HISTORY, SUBVERSION AND SELF-SUBVERSION: THE CURIOUS CASES OF JEAN MABILLON AND RICHARD SIMON (I/II) - LAZĂR, Veronica (Studia Universitatis Babeș-Bolyai Philosophia, 2020)
This paper compares two programmes of historical criticism at the end of the 16th Century – Jean Mabillon’s diplomatics and Richard Simon’s biblical criticism. Although they were both conceived as philological and contextual reconstruction of texts, their relation with the authority of the texts and their engagement with political and institutional stakes were strikingly different.